Experimental study of aluminium chips to find out temperature distribution. (2023) - Ohol, Sandeep; Mathew, V.K.; Bhojwani, Virendra; Sanap, Sudarshan; Kakade, Manishant
Abstract: The current study examines the impact of natural convective heat transfer on five identical discrete IC chips (Aluminium) mounted on a Bakelite substrate board. At various locations on the substrate board, the IC chips are exposed to 2500 W/mm 2 and 3700 W/mm 2 uniform and non-uniform heat fluxes, respectively. The temperatures of the five IC chips varied despite the uniform heat flow provided. The source of heat 1. The temperature of IC chips on the substrate board is influenced by their size, shape, and placement. The findings show that the thermal interaction of the IC chips is difficult to control and that the position of the IC chips is critical in cooling.